Pengaruh Perdagangan antara Indonesia-Mesir terhadap Pertumbuhan Ekonomi Indonesia Tahun 2017-2022 dalam Perspektif Ekonomi Islam - Nikita Zulyan Batubara; Hotbin Hasugian; Imsar Imsar (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of trade between Indonesia and Egypt on Indonesia's economic growth in the view of Islamic economics. The research uses a quantitative approach with multiple linear regression equipped with export-import data from the Ministry of Trade and economic growth data from BPS in 2017-2022. The results of the study are partially the Indonesian export variable to Egypt has a negative and significant effect, and the import variable to Egypt has a positive and significant effect on Indonesia's economic growth. As well as simultaneous test results, Indonesian exports to Egypt and Egyptian imports to Indonesia simultaneously have a significant effect on Indonesia's economic growth. Keywords: Export; Import; Economic Growth